(untitled) (Revista Española de Fisiología, 1973)
The liberation of PF-4 under the action of ADP, thrombin and collagen fibres has been determined in human platelet rich plasma. Platelet aggregation was first induced with the different agents, and then the PF-4 liberated during the aggregation was evaluated. Thrombin, at concentrations which imply a strong plasma coagulation, causes a nearly complete liberation of PF-4 since it is accompanied by a platelet lysis. However, lower concentrations of thrombin such as to cause a weak plasmatic coagulation and/or a reversible platelet aggregation, only provokes a partial liberation of PF-4. High concentrations of ADP only produce a partial liberation of PF-4, with presence of some refractory cases which do not respond to the liberating stimulus. The ADP, when causing a reversible platelet aggregation, does not provoke the liberation of PF-4. Collagen fibres produce a strong liberation of PF-4 similar to the one obtained with high concentrations of thrombin.